Abu a-Qasim al-Zahrawi's contribution to neurosurgery - Mohamad Asharaf, Asfana Banu; Shuriye, Abdi Omar (IIUM Press, 2011)
This chapter investigates AI-Zahrawi's contribution to surgery especially neurosurgery. The main objective of this chapter is to study AI-Zahrawis' views on neurosurgery operation. Neurosurgery is concerned on causes of brain diseases, spine, peripheral nerves, and arteries of the neck. Abu AI-Qasim AI-Zahrawi was born in 936 C.E. in city Zahra of Cordoba. He was regarded as the father of modem surgery and his Kitab al-Tasrif (Book of Confessions) which consists of 30 volumes was translated into various European languages and used in medical schools.